The international river interface cooperative: Public domain flow and morphodynamics software for education and applications. (July 2016) - Nelson, Jonathan M.; Shimizu, Yasuyuki; Abe, Takaaki; Asahi, Kazutake; Gamou, Mineyuki; Inoue, Takuya; Iwasaki, Toshiki; Kakinuma, Takaharu; Kawamura, Satomi; Kimura, Ichiro; Kyuka, Tomoko; McDonald, Richard R.; et al.
Highlights: New public domain flow and morphodynamics interface for river applications. Interface includes one-, two- and three-dimensional flow and bed deformation solvers. Comprehensive tools for grid and mesh generation, plus visualization of solutions. Abstract: This paper describes a new, public-domain interface for modeling flow, sediment transport and morphodynamics in rivers and other geophysical flows. The interface is named after the International River Interface Cooperative (iRIC), the group that constructed the interface and many of the current solvers included in iRIC. The interface is entirely free to any user and currently houses thirteen models ranging from simple one-dimensional models through three-dimensional large-eddy simulation models. Solvers are only loosely coupled to the interface so it is straightforward to modify existing solvers or to introduce other solvers into the system. Six of the most widely-used solvers are described in detail including example calculations to serve as an aid for users choosing what approach might be most appropriate for their own applications. The example calculations range from practical computations of bed evolution in natural rivers to highly detailed predictions of the development of small-scale bedforms on an initially flat bed. The remaining solvers are also briefly described. Although the focus of most solvers is coupled flow and morphodynamics, several of the solvers are also specifically aimed at providing flood inundation predictions over large spatial domains. Potential users can download the application, solvers, manuals, and educational materials including detailed tutorials atwww.-i-ric.org . The iRIC development group encourages scientists and engineers to use the tool and to consider adding their own methods to the iRIC suite of tools.